Creative communications campaign fostering social learning loops - Harvey, Blane; Ensor, Jonathan; Garside, Ben; Woodend, John; Naess, Lars Otto; Carlile, Liz (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Kabarole Research Centre (KRC, an NGO) started a radio food security awareness raising campaign for farmer groups in Western Uganda. More than 144 radio drama series on the topic of food security were performed and aired on radio as an entertaining means of discussing the topic. Listener demand shaped the shows through on-air phone-ins that led to the formation of local listeners clubs. The topic of granary stores was a key demand and more active listeners clubs such as that in Mugusu Kyagwamwoha invited KRC to facilitate a social learning process that led to granary stores suited to their community, in particular using local building materials. Wider community learning on the issue was fostered by the listeners club themselves performing radio dramas to their own community, building demonstration granaries, and building institutional support for learning processes on granaries and food security at the community level. The NGO has also learned much in terms of its potential to foster social learning processes by adapting its own approaches to research.